Modeling optimal combination of breast and cervical cancer screening strategies in China - Xuewei Liu; Yanbo Wang; Bei Gao; Xinlin Lu; Yuan Wang; Wenli Lu (BMC Women's Health)
Abstract Background Breast and cervical cancers are the commonest cancers among women. Secondary prevention of cancer through screening minimizes disease burden and improves survival outcomes. Optimizing screening strategies for breast and cervical cancers is a challenge in resource-limited settings with a high population density such as China. Therefore, we aimed at assessing the efficiency of different combined screening strategies for breast and cervical cancers under different budgets in China. Methods Markov cohort model was used to evaluate the cost-effectiveness of 36 strategy combinations for breast and cervical cancer screening with varying screening modality and intervals. The results were used as inputs in the Integer Programming (IP) model to determine the combination of the different screening options under different budgets. Results The optimal combination strategy was biennial breast ultrasonography (BUS) and mammography (MAM) in parallel screening and quinquennial human papillomavirus (HPV) for breast and cervical cancer screening under the threshold of the annual per capita social cost investment (PCSCI) (18.80 USD) in China. Using this strategy, the total investment cost for 100,000 females was 1,877,984.50 USD, and the incremental life-years compared with no screening was 3,122 life-years. The optimal combination strategy included annual clinical breast examination (CBE), BUS and MAM in series screening, and biennial thin-layer liquid-based cytology (TCT) and HPV in series screening with the annual PCSCI reaching 37.60 USD. Thereafter, as the cost input continued to increase, the optimal combination strategy remained unchanged, and the sum of incremental life-years and actual input costs did not increase. Conclusions From a social cost–benefit perspective, biennial BUS and MAM in parallel screening, and quinquennial HPV screening is the most efficient combination strategy with limited budget, while annual CBE, BUS and MAM in series screening and biennial TCT and HPV in series screening are the most efficient combination strategy with sufficient budget.